Combustion performance and pollutant emissions analysis using diesel/gasoline/iso-butanol blends in a diesel engine. (1st October 2017) - Wei, Mingrui; Li, Song; Xiao, Helin; Guo, Guanlun
Highlights: The diesel/gasoline/iso-butanol blends were investigated in a CI engine. Blend with gasoline or iso-butanol produce higher HC emission. CO increase at low loads and decrease at medium and high loads with blend fuels. Gasoline or iso-butanol decrease large particles but increase small particles. Blend fuels reduce total PM number and mass concentrations. Abstract: In this study, the effects of diesel/gasoline/iso-butanol blends, including pure diesel (D100), diesel (70%)/gasoline (30%) (D70G30, by mass), diesel (70%)/iso-butanol (30%) (D70B30) and diesel (70%)/gasoline (15%)/iso-butanol (15%) (D70G15B15), on combustion and exhaust pollutant emissions characteristics in a four-cylinder diesel engine were experimentally investigated under various engine load conditions with a constant speed of 1800 rpm. The results indicated that D70G30, D70G15B15 and D70B30 delayed the ignition timing and shortened the combustion duration compared to D100. Additionally, CA50 was retarded when engine fuelled with D70G30, D70G15B15 and D70B30 at low engine load conditions, but it was advanced at medium and high engine loads. The maximum pressure rise rates (MPRRs) of D70G30, D70G15B15 and D70B30 were increased compared with D100 except for at engine load of 0.13 MPa BMEP (brake mean effective pressure). Meanwhile, D70G15B15 and D70B30 produced higher brake specific fuel consumption (BSFC) than that of D100. The effects of diesel blend with gasoline or iso-butanol on exhaust pollutant emissions were varied with loads. CO emissions were increased obviously and NOx emissions were decreased under low engine loads. However, CO emissions were decreased and NOx emissions were slightly increased under the medium and high engine load conditions. However, D70G30, D70G15B15 and D70B30 leaded to higher HC emissions than D100 regardless the variation of engine load. Moreover, the particulate matter (PM) (diameter, number and mass concentrations) emissions by using D70G30, D70G15B15 and D70B30 were significantly reduced compared to D100, but more small-size particles were produced.